Preparing for the era of the digitally transparent supply chain: A call to research in a new kind of journal - Robert B. Handfield (Logistics, 2017)
We are commencing a new era in global trade: the era of the digitized supply chain. In the 25 years I have taught students and conducted research in the field of supply chain management, I have never seen such a magnitude of change as is occurring today. These changes are unparalleled in their scope, the implications for revision of the way humans work is completely new, and the impacts they will have will be both business-transformative and life-changing. This is the era of the transparent, real-time supply chain, which is being enabled by the rapid digitization of the communication infrastructure, cloud-based computing, mobile technology, and the rise of the digital ecosystem. Interestingly, these changes have less to do with technology, but rather our mindset and thinking on how to deal with them. In this essay, I argue that we need a new type of journal to advance the discipline, as the current ones simply aren't keeping up.
Keywords: 650